Cotton Production in Armenia (Before the Establishment of the Soviet Regime) - Mikaelyan, Mikael Varazdat (ՀՀ ԳԱԱ ՏԻ)
The centuries-old experience of cotton cultivation (as well as agriculture development) in Armenia has shown that the country has achieved success in this area when there was state support and promotion. In conditions of external competition, agriculture (especially cotton cultivation) cannot record significant development without a solid government support strategy. Even today, in conditions of insufficient support from the state, the farmer feels insecure while employing this very important activity for the country. The purpose of the study is to present the evolution of cotton cultivation in Armenia and the importance of state support for this agriculture sub-sector. Актуальность исследования. Многовековой опыт выращивания хлопка (а также развития сельского хозяйства) в Армении показал, что страна добилась успеха в этой области, когда государство поддерживало и способствовало ее развитию. В условиях внешней конкуренции сельское хозяйство (особенно хлопководство) не может существенно развиваться без солидной программы государственной поддержки. Цель исследования – показать эволюцию выращивания хлопка в Армении и важность государственной поддержки этой отрасли сельского хозяйства. Հայաստանում բամբակենու մշակման (ինչպես նաև գյուղատնտեսության զարգացման) դարավոր փորձը ցույց է տվել, որ երկիրն այս բնագավառում հաջողություններ է ունեցել, երբ պետությունը աջակցել և խթանել է դրա զարգացումը: Արտաքին մրցակցության պայմաններում գյուղատնտեսությունը (հատկապես բամբակագործությունը), առանց պետական աջակցության հիմնավոր ծրագրի, էապես զարգացնել հնարավոր չէ: Հետազոտության նպատակն է ցույց տալ Հայաստանում բամբակենու մշակության էվոլյուցիան և գյուղատնտեսության այս ոլորտին պետական աջակցության կարևորությունը:
Keywords: Cotton cultivation; Armenia